Public Service Innovation Policy at The Communication and Informatics Department of East Java Province through Total Quality Management (TQM) Practices - Assyari, Assyari; Handoko, Rudy; Darmawan, Arif (LPPM of NAROTAMA UNIVERSITY, 2023)
In an effort to improve the quality of public services, the Ministry of Communication and Information (KOMINFO) has held a One Day Service (ODS) or public service automation. The results of the implementation of the ODS have had a significant impact on accelerating the service process, but complaints about discrepancies or discrepancies in data are still common, the president even issued Presidential Regulation no. 39 of 2019 concerning one Indonesian data as a result of gaps in data between government agencies and data provider agencies such as the Central Statistics Agency (BPS). So the purpose of this study is to analyze data integration efforts and their constraints, as well as to design a data integration approach model that is seen as more effective and optimal. This descriptive qualitative research collects document data and interviews with informants who are employees at Kominfo regarding data integration efforts, and the analysis is carried out using a member check and FGD triangulation approach. The results of the research show that the process of integrating data is still not optimal, constrained by problems of coordination between agencies that have not been well established, and Kominfo is still focused on aspects of strengthening technological infrastructure, as well as the readiness of several agencies to supply data. Model construction analysis found that the total quality management (TQM) approach led to an increase in the potential of the Ministry of Communication and Informatics to carry out collaboration and collaboration to obtain data, analyze and publish data needed by society, organizations and the industrial sector. This integration can be carried out optimally when using integrated management, namely TQM.